Gold Nanoparticles Based Optical Biosensors for Cancer Biomarker Proteins: A Review of the Current Practices - Tai, Jinghua; Fan, Shuang; Ding, Siqi; Ren, Lishen (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer prognosis depends on the early detection of the disease. Gold nanoparticles (AuNPs) have attracted much importance in biomedical research due to their distinctive optical properties. The AuNPs are easy to fabricate, biocompatible, surface controlled, stable, and have surface plasmonic properties. The AuNPs based optical biosensors can intensely improve the sensitivity, specificity, resolution, penetration depth, contrast, and speed of these devices. The key optical features of the AuNPs based biosensors include localized surface plasmon resonance (LSPR), SERS, and luminescence. AuNPs based biomarkers have the potential to sense the protein biomarkers at a low detection level. In this review, the fabrication techniques of the AuNPs have been reviewed. The optical biosensors based on LSPR, SERS, and luminescence are also evaluated. The application of these biosensors for cancer protein detection is discussed. Distinct examples of cancer research that have a substantial impact on both scientific and clinical research are presented.